The anti-fouling activity of solvothermally synthesized Nb2O5-coated Fe ship strip on optimal interactions at the targeted interfaces of barnacle attachments -An Insilico study - Aravindhan Vanangamudi; Sathyanarayanan Punniyakoti (Materials Research Express)
Fouling is a major issue occurring in water-going vessels, such as ships that cause increased surface roughness and drag resistance. The fouling organisms produce extracellular polymeric substances (EPS), which negatively impact water-going vessels. The settlement-inducing protein complex (SIPC) is a contact pheromone that promotes the gregarious settling of barnacle larvae (cyprids). The SIPC can be found in both adult barnacle cuticles and cyprids as transient adhesive secretions (footprints). The presence of SIPC in the footprints plays a critical role during the initial adhesion, which facilitates further settlement. The adsorption of of SIPC on Iron/Fe ship strip(FSS) surface was often found to be irreversible even after physical treatements. For the antifouling studies, Nb _2 O _5 coated FSS were constructed and simulated to analyze the interaction of barnacles Aacp20K protein. For simulation studies, the homology model of barnacles Aacp20K protein is fabricated using the SWISS automated comparative modeling platform. The result of homology model showed a good 3D secondary structure of Aacp20K protein, especially 7q1y template protein. Adsorption location analysis results illustrate that the surface of the FSS coated with Nb _2 O _5 film disfavour the binding of SIPC inhibiting the binding of barnacle cuticles and cyprids. For validating the simulation results, Nb _2 O _5 nanostructure film was synthesized using a solvothermal process and characterized using XRD,SEM and EDS. Furthermore, the wetting behaviour was studied experimentally. The simulations and experimental results indicate Nb _2 O _5 -coated FSS as potent anti-fouling surfaces.